ISSUES OF THE INFLUENCE OF THE FINANCIAL SECTOR ON ECONOMIC GROWTH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
The article analyzes scientific sources on the study of the influence of the financial sector on economic growth, and considers the specific aspects of the influence of the financial market on economic growth.